The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad420
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Academic Development

Abstract: Adaptability refers to an individual's adjustments of their thoughts, behaviors, and emotions in the face of new, changing, or uncertain situations or events. The adolescent period represents one of the most rapid phases of human development, where significant and interrelated physical, neurodevelopmental, psychosocial, and environmental changes occur concomitantly with important changes in the educational environment. This entry examines the role of adaptability in adolescent academic development—through seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Adaptability is also grounded in lifespan theory of control (Heckhausen et al, 2010) and individual functioning approaches (Buss and Cantor, 1989), whereby students make necessary modifications in order to function more positively in one's environment. It follows then, that adaptability is of importance across the lifespan (Martin et al, 2012), and has been found to yield positive effects for different sample groups in a number of contexts (e.g., among students, teachers, teaching assistants, and others working in organizational settings, Holliman et al, 2019Holliman et al, , 2020Martin et al, 2019).…”
Section: Adaptabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptability is also grounded in lifespan theory of control (Heckhausen et al, 2010) and individual functioning approaches (Buss and Cantor, 1989), whereby students make necessary modifications in order to function more positively in one's environment. It follows then, that adaptability is of importance across the lifespan (Martin et al, 2012), and has been found to yield positive effects for different sample groups in a number of contexts (e.g., among students, teachers, teaching assistants, and others working in organizational settings, Holliman et al, 2019Holliman et al, , 2020Martin et al, 2019).…”
Section: Adaptabilitymentioning
confidence: 99%
“…A developing literature has shown that adaptability is predictive of Students' academic outcomes across education sectors (see Holliman et al, 2020), and is also a critical element of (secondary, pre-16) Students' psychological wellbeing, as indicated by measures of self-esteem, life satisfaction, and sense of meaning and purpose (Martin et al, 2013). A common finding, which is compatible with the COR theory and model, is that adaptability may impact upon these important outcomes via behavioral engagement; specifically, students higher in adaptability are more likely to self-regulate in other situations, such as those involving task management or persistence (positive behaviors) whereas students lower in adaptability are more likely to maneuver defensively, by self-sabotaging or by disengaging (negative behaviors), in anticipation of lower self-efficacy and poorer performance (Martin et al, 2013).…”
Section: Adaptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptability refers to the ability of firms to respond positively and appropriately to changing environmental situations (Holliman et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%